The effect of recreational therapy application on fatigue in hemodialysis patients: a randomized clinical trial - Moein Alishahi; Seyed Reza Mazloum; Samira Mohajer; Mohammad Namazinia (BMC Nephrology, 2024)
Abstract Background Chronic Kidney Disease (CKD) is a progressive disorder that often leads to End-Stage Renal Disease (ESRD), necessitating hemodialysis (HD) treatment. Fatigue is a prevalent and debilitating symptom among HD patients, significantly affecting their quality of life. Recreational Therapy (RT) is a therapeutic recreational service designed to maintain and restore a person’s level of performance and independence in daily activities. This study aimed to evaluate the effect of a smartphone-based recreational therapy intervention on fatigue in hemodialysis patients. Methods This randomized controlled trial was conducted on HD patients at a hospital in Mashhad, Iran. The intervention group received a custom-designed recreational therapy mobile application, including music, comedy, exercise, and educational content. The control group received standard care. Fatigue was assessed using the Multidimensional Fatigue Inventory (MFI-20) before and after the 30-day intervention. Results A total of 72 patients (36 per group) participated in the study. The intervention group demonstrated a significant reduction in overall fatigue scores and improvements across various fatigue dimensions, including general fatigue, physical fatigue, mental fatigue, reduced activity, and reduced motivation, compared to the control group (p < 0.001). Conclusion The smartphone-based recreational therapy intervention effectively reduced fatigue in hemodialysis patients. This approach could be a valuable complementary strategy for managing fatigue in this population. Further research is needed to explore the long-term sustainability of these benefits and the intervention’s impact on other patient-reported outcomes. Trial registration This study was registered in the Iranian Registry of Clinical Trials (no. IRCT20220803055608N1) on 29/08/2022.